Metabolic adaptations induced by long-term fasting in quails - Sartori, D. R S [UNESP]; Migliorini, R. H.; Veiga, J. A S [UNESP]; Moura, J. L. [UNESP]; Kettelhut, I. C.; Linder, C. [UNESP] (Elsevier, 1995)
After up to 21 days without food, adult male quails (Coturnix coturnix japonica) lost about 45% of the initial body weight (100-150 g). As in naturally fast-adapted and larger birds, three phases were identified during prolonged fasting in quails. Phase I lasted 2-3 days and was characterized by a rapid decrease in the rate of body weight loss and high fat mobilization. Phase II was longer and characterized by a slow and steady decline in the rates of body weight loss and of nitrogen excretion. The third (critical) period was marked by an abrupt increase in the rates of body weight loss and of nitrogen excretion. Despite their small size, the duration of phase II in quails was relatively long, a clear advantage for the study of the relationships between the several metabolic events that occur during this crucial adaptative period. Also, the beginning of phase III could be precisely determined. Changes in blood glucose, plasma FFA and triacylglycerols levels, as well as in liver and carcass lipid content were similar to those found in other species of birds. Therefore, quails seem to be a suitable model to investigate the biochemical mechanisms involved in the metabolic adjustments to prolonged food deprivation in non fasting-adapted birds. © 1995.
Keywords: Body weight; Carcass lipid; FFA; Glucose; Liver; Nitrogen excretion; Plasma amino acids; Triacylglycerols; amino acid; fatty acid; glucose; nitrogen; triacylglycerol; adolescent; animal experiment; caloric restriction; controlled study; male; metabolism; nonhuman; priority journal; quail; Adaptation, Physiological; Amino Acids; Animal; Blood Glucose; Body Weight; Coturnix; Dietary Carbohydrates; Dietary Proteins; Fasting; Fatty Acids, Nonesterified; Lipids; Male; Nitrogen; Support, Non-U.S. Gov't; Triglycerides; Coturnix coturnix